IMPLEMENTASI AKTIVITAS LITERASI DI SMA NEGERI BATUSANGKAR - Mutia, Puput; Atmazaki, Atmazaki,; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTÂ The purposes of this study are (1) to know the literacy activities in SMA N Batusangkar, (2) to describe the implementation of school literacy activities in SMA N Batusangkar, (3) to describe the supporting and inhibiting factors of the implementation of school literacy activities in SMA N Batusangkar. This Study was conducted on schools that have implemented literacy programs. The data in this study are the results of interviews on people in SMA N Batusangkar who are involved in the literacy activities that consist of the head of the library, curriculum representatives, indonesian language teacher, other subject teachers, and two Randomly selected students. The finding of this study are (1) SMA Negeri 1 Batusangkar, SMA Negeri 2 Batusangkar, and SMA Negeri 3 Batusangkar had been carrying out literacy activities at the school, (2) SMA Negeri Batusangkar implement literacy activities based on two basic literacy components, namely basic literacy and literacy library (3) SMA Negeri Batusangkar uses two components dasat literacy literacy activities at all stages, namely conditioning phase of activity, the activity of the development stage, and the activity stage of learning.Â Kata kunci: Implementasi, aktivitas, literasi, SMA Negeri Batusangkar